2022
DOI: 10.3390/jcm11144085
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Inflammatory Markers and the Risk of Postoperative Delirium in Patients Undergoing Lumbar Spinal Fusion Surgery

Abstract: We investigated the possible associations between postoperative delirium (POD) and routinely available preoperative inflammatory markers in patients undergoing lumbar spinal fusion surgery (LSFS) to explore the role of neuroinflammation and oxidative stress as risk factors for POD. We analyzed 11 years’ worth of data from the Smart Clinical Data Warehouse. We evaluated whether preoperative inflammatory markers, such as the neutrophil-to-lymphocyte ratio (NLR), the monocyte-to-lymphocyte ratio (MLR), and the CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…[ 26 ] Additionally, evidence suggests that preoperative inflammatory markers, including IL-6, IL-8, IL-10, and IL-1β, as well as TNF-α, are correlated with the occurrence of POD in patients undergoing surgical procedure. [ 27 ] Furthermore, genome-wide DNA methylation profiles have been studied among neurosurgery patients with and without postoperative delirium, demonstrating heightened inflammatory cytokines such as IL‐1β, IL‐6, and TNF-α in the brain following surgical intervention. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 26 ] Additionally, evidence suggests that preoperative inflammatory markers, including IL-6, IL-8, IL-10, and IL-1β, as well as TNF-α, are correlated with the occurrence of POD in patients undergoing surgical procedure. [ 27 ] Furthermore, genome-wide DNA methylation profiles have been studied among neurosurgery patients with and without postoperative delirium, demonstrating heightened inflammatory cytokines such as IL‐1β, IL‐6, and TNF-α in the brain following surgical intervention. [ 28 ]…”
Section: Discussionmentioning
confidence: 99%
“…[26] Additionally, evidence suggests that preoperative inflammatory markers, including IL-6, IL-8, IL-10, and IL-1β, as well as TNF-α, are correlated with the occurrence of POD in patients undergoing surgical procedure. [27] Furthermore, genome-wide DNA methylation profiles have been studied among neurosurgery patients with and without postoperative delirium, demonstrating heightened inflammatory cytokines such as IL-1β, IL-6, and TNF-α in the brain following surgical intervention. [28] These findings collectively emphasize the intricate relationship between inflammatory cytokines and the development of postoperative delirium, shedding light on the potential role of Dexmedetomidine in modulating the inflammatory response and its impact on POD.…”
Section: Relevance To Existing Dexmedetomidine Researchmentioning
confidence: 99%
“…Although the correlation between GA exposure and an elevated risk of POD remains controversial [18][19][20][21][22][23] , it is generally believed that GA exposure would lead to an increased risk of POD; however, a large-scale RCT that randomly assigned patients to either GA or spinal anesthesia did not find any difference in the incidence of POD between the two groups 44 , suggesting no causality between GA exposure and the subsequent POD. On the other www.nature.com/scientificreports/ hand, several studies reported an association of a proinflammatory state with the development of POD [45][46][47] , highlighting inflammation as a potential underlying mechanism. Consistently, a previous meta-analysis of 54 observational studies revealed significantly increased circulating C-reactive protein and interleukin-6 concentrations in patients with POD 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CAR, Yang et al indicated that preoperative CAR was not related to the occurrence of POD in cases undergoing lumbar spinal surgery (40). Peng et al found that preoperative CAR was a significant predictor for POD for older patients receiving total joint arthroplasty (41).…”
Section: Carmentioning
confidence: 99%